Parsimonious cumulative process-based workflow for early sanitation infrastructure evaluation (CPESI): Case study of Riohacha, Colombia - (:unkn) unknown (Elsevier BV, 2024)
In small and medium-sized cities from developing countries, the early selection of integrated wastewater management systems is challenging due to the lack or limitations in the availability of basic information and skilled professionals. This study prese...
Keywords: Infraestructura sanitaria; Saneamiento